Lec2 Math
Lec2 Math
Lec2 Math
Emad Al-Hemiary
Second Year, First Semester 2021-2022
Example 2.3: What are the domain and range for the following functions of three variable?
Solution:
Function Domain Range
→ 𝑎𝑙𝑙 𝑣𝑎𝑙𝑢𝑒𝑠 𝑜𝑓 𝑥
𝑤 should be real 𝑎𝑛𝑑 𝑎𝑙𝑙 𝑣𝑎𝑙𝑢𝑒𝑠 𝑜𝑓 𝑦 The result of
𝑤 = √𝑥 2 + 𝑦 2 + 𝑧 2 value 𝑤
[0, ∞)
𝑎𝑛𝑑 𝑎𝑙𝑙 𝑣𝑎𝑙𝑢𝑒𝑠 𝑜𝑓 𝑦
(𝑒𝑛𝑡𝑖𝑟𝑒 𝑠𝑝𝑎𝑐𝑒)
1 𝑤 should be real The result of
𝑤= value not infinite
→ (𝑥, 𝑦, 𝑧) ≠ (0,0,0) (0, ∞)
𝑥2 + 𝑦2 + 𝑧2 𝑤
→ 𝑧 𝑠ℎ𝑜𝑢𝑙𝑑 𝑏𝑒 𝑝𝑜𝑠𝑖𝑡𝑖𝑣𝑒
𝑤 should be real The result of
𝑤 = 𝑥𝑦 ln 𝑧 𝑖. 𝑒, ℎ𝑎𝑙𝑓 𝑠𝑝𝑎𝑐𝑒 𝑧 > 0 (−∞, ∞)
value not infinite 𝑤
1
Engineering Mathematics I Lecture 2: Partial Derivatives Prof. Dr. Emad Al-Hemiary
Second Year, First Semester 2021-2022
Limits:
1) We say that a function 𝑓(𝑥, 𝑦) approaches the limit 𝐿 as (𝑥, 𝑦) approaches (𝑥0 , 𝑦0 ) and
write:
lim 𝑓(𝑥, 𝑦) = 𝐿
(𝑥,𝑦)→(𝑥0 ,𝑦0 )
2) If, for every number 𝜖 there exists a corresponding number 𝛿 such that for all (𝑥, 𝑦) in
the domain of 𝑓,
2
Engineering Mathematics I Lecture 2: Partial Derivatives Prof. Dr. Emad Al-Hemiary
Second Year, First Semester 2021-2022
Since the Quotient rule does not apply, try to manipulate and cancel the denominator. If
multiply by (√𝑥 + √𝑦), then:
Continuity:
A function 𝑓(𝑥, 𝑦) is continuous at the point (𝑥0 , 𝑦0 ) if:
1) 𝑓 is defined at (𝑥0 , 𝑦0 ).
2) lim 𝑓(𝑥, 𝑦) exists
(𝑥,𝑦)→(𝑥0 ,𝑦0 )
3) lim 𝑓(𝑥, 𝑦) = 𝑓(𝑥0 , 𝑦0 )
(𝑥,𝑦)→(𝑥0 ,𝑦0 )
3
Engineering Mathematics I Lecture 2: Partial Derivatives Prof. Dr. Emad Al-Hemiary
Second Year, First Semester 2021-2022
Solution:
We follow the three conditions listed above:
1) For every point (𝑥, 𝑦) other than (0,0),
𝑓 is defined by value. For example: 𝑓(0,1) = 0
2) Since lim 𝑓(𝑥, 𝑦) exists, 𝑓 has definite value
(𝑥,𝑦)≠(𝑥0 ,𝑦0 )
3) At (0, 0), the value of 𝑓 is defined, but 𝑓,
we claim, has no limit as (𝑥, 𝑦) → (0,0).
The reason is that different paths of approach to the origin can lead to different results,
as we now see.
𝐿𝑒𝑡 𝑦 = 𝑚𝑥 (𝑚 is an arbitrary value), the:
2𝑥𝑦 2𝑥(𝑚𝑥) 𝑥 2 (2𝑚) 2𝑚
𝑓(𝑥, 𝑦)|𝑦=𝑚𝑥 = 2 | = = =
𝑥 + 𝑦 2 𝑦=𝑚𝑥 𝑥 2 + (𝑚𝑥)2 𝑥 2 (1 + 𝑚2 ) 1 + 𝑚2
Therefore, 𝑓 has this number as its limit as (𝑥, 𝑦) approaches (0, 0) along the line:
2𝑥𝑦 2𝑚
lim 𝑓(𝑥, 𝑦) = lim 2 2
| =
(𝑥,𝑦)→(𝑥0 ,𝑦0 ) (𝑥,𝑦)→(𝑥0 ,𝑦0 ) 𝑥 + 𝑦
𝑦=𝑚𝑥
1 + 𝑚2
𝑎𝑙𝑜𝑛𝑔 𝑦=𝑚𝑥
This limit changes with 𝑚. There is therefore no single number we may call the limit of 𝑓
as (𝑥, 𝑦) approaches the origin. The limit fails to exist, and the function is not continuous.
Therefore:
2𝑘
lim 𝑓(𝑥, 𝑦) = lim 𝑓(𝑥, 𝑦)|𝑦=𝑘𝑥 2 =
(𝑥,𝑦)→(𝑥0 ,𝑦0 ) (𝑥,𝑦)→(𝑥0 ,𝑦0 ) 1 + 𝑘2
𝑎𝑙𝑜𝑛𝑔 𝑘𝑥 2
4
Engineering Mathematics I Lecture 2: Partial Derivatives Prof. Dr. Emad Al-Hemiary
Second Year, First Semester 2021-2022
This limit varies with the path of approach. If (𝑥, 𝑦) approaches (0, 0) along the parabola for
instance, and the limit is 1. If (𝑥, 𝑦) approaches (0, 0) along the x-axis, and the limit is 0. By the
two-path test, 𝑓 has no limit as (𝑥, 𝑦) approaches (0, 0).
Similarly,
𝜕𝑓 𝑑 𝑓(𝑥0 , 𝑦0 + ℎ) − 𝑓(𝑥0 , 𝑦0 )
| = 𝑓(𝑥0 , 𝑦)| = lim , 𝑝𝑟𝑜𝑣𝑖𝑑𝑒 𝑡ℎ𝑎𝑡 𝑡ℎ𝑒 𝑙𝑖𝑚𝑖𝑡 𝑒𝑥𝑖𝑠𝑡𝑠
𝜕𝑦 (𝑥 𝑑𝑦 ℎ→0 ℎ
0 ,𝑦0 ) 𝑦=𝑦
0
Notations:
𝜕𝑓
𝑖𝑠 𝑡ℎ𝑒 𝑠𝑎𝑚𝑒 𝑎𝑠 𝑓𝑥
𝜕𝑥
𝜕𝑓
𝑖𝑠 𝑡ℎ𝑒 𝑠𝑎𝑚𝑒 𝑎𝑠 𝑓𝑦
𝜕𝑦
5
Engineering Mathematics I Lecture 2: Partial Derivatives Prof. Dr. Emad Al-Hemiary
Second Year, First Semester 2021-2022
𝜕𝑓 𝜕𝑓
Example 2.9: Find the partial derivatives 𝜕𝑥 𝑎𝑛𝑑 of 𝑓(𝑥, 𝑦) = (2𝑥 − 3𝑦)2 at a point (4,2)
𝜕𝑦
Solution:
𝜕𝑓 𝜕
= (2𝑥 − 3𝑦)2 = 2(2)(2𝑥 − 3𝑦)|(4,2) = 4{2(4) − 3(2)} = 8
𝜕𝑥 𝜕𝑥
𝜕𝑓 𝜕
= (2𝑥 − 3𝑦)2 = 2(−3)(2𝑥 − 3𝑦)|(4,2) = −6{2(4) − 3(2)} = −12
𝜕𝑦 𝜕𝑦
𝜕𝑓 𝜕𝑓
Example 2.10: Find the partial derivatives 𝜕𝑥 𝑎𝑛𝑑 of 𝑓(𝑥, 𝑦) = 𝑦 sin 𝑥𝑦
𝜕𝑦
Solution:
𝜕𝑓 𝜕 𝜕
= 𝑦 sin 𝑥𝑦 = 𝑦 sin 𝑥𝑦 = 𝑦(𝑦) cos 𝑥𝑦 = 𝑦 2 cos 𝑥𝑦
𝜕𝑥 𝜕𝑥 𝜕𝑥
𝜕𝑓 𝜕 𝜕 𝜕
= 𝑦 sin 𝑥𝑦 = 𝑦 sin 𝑥𝑦 + sin 𝑥𝑦 𝑦 = 𝑥𝑦 cos 𝑥𝑦 + sin 𝑥𝑦
𝜕𝑦 𝜕𝑦 𝜕𝑦 𝜕𝑦
𝜕𝑧
Example 2.11: Find the partial derivative 𝜕𝑥 of 𝑦𝑧 − ln 𝑧 = 𝑥 + 𝑦. (Note: 𝑧 is a function of 𝑥 and
𝑦)
Solution:
𝜕𝑧
We apply 𝜕𝑥 to both sides:
𝜕 𝜕 𝜕𝑧 1 𝜕𝑧 𝜕𝑧 1 𝜕𝑧 1 𝜕𝑧 𝑧
(𝑦𝑧 − ln 𝑧) = (𝑥 + 𝑦) → 𝑦 − =1+0→ (𝑦 − ) = 1 → = → =
𝜕𝑥 𝜕𝑥 𝜕𝑥 𝑧 𝜕𝑥 𝜕𝑥 𝑧 𝜕𝑥 𝑦 − 1 𝜕𝑥 𝑦𝑧 − 1
𝑧
Example 2.12: Find the partial derivative of 𝑓(𝑥, 𝑦, 𝑧) = 𝑥 sin(𝑦 + 3𝑧) with respect to z. (Note:
𝑥, 𝑦, 𝑧 are independent)
Solution:
𝜕 𝜕 𝜕
𝑥 sin(𝑦 + 3𝑧) = 𝑥 cos(𝑦 + 3𝑧) = 𝑥 cos(𝑦 + 3𝑧) (𝑦 + 3𝑧) = 3𝑥 cos(𝑦 + 3𝑧)
𝜕𝑧 𝜕𝑧 𝜕𝑧
6
Engineering Mathematics I Lecture 2: Partial Derivatives Prof. Dr. Emad Al-Hemiary
Second Year, First Semester 2021-2022
𝜕 2𝑓 𝜕 𝜕𝑓
= ( ) 𝑑 𝑠𝑞𝑢𝑎𝑟𝑒𝑑 𝑓 𝑑𝑦 𝑑𝑥 𝑓𝑦𝑥 𝑓 𝑠𝑢𝑏 𝑦𝑥
𝜕𝑥𝜕𝑦 𝜕𝑥 𝜕𝑦
Differentiate first with respect to y, then with respect to x.
𝜕 2𝑓 𝜕 𝜕𝑓
= ( ) 𝑑 𝑠𝑞𝑢𝑎𝑟𝑒𝑑 𝑓 𝑑𝑥 𝑑𝑦 𝑓𝑥𝑦 𝑓 𝑠𝑢𝑏 𝑥𝑦
𝜕𝑦𝜕𝑥 𝜕𝑦 𝜕𝑥
Differentiate first with respect to x, then with respect to y.
Example 2.13: Find the second-order partial derivatives: 𝑓𝑥𝑥 , 𝑓𝑦𝑦 , 𝑓𝑦𝑥 , and 𝑓𝑥𝑦 of 𝑓(𝑥, 𝑦) =
𝑥 cos 𝑦 + 𝑦𝑒 𝑥
Solution:
𝜕 𝜕 𝜕 𝜕 𝜕 𝜕 𝜕 𝜕
𝑓𝑥𝑥 = { (𝑥 cos 𝑦 + 𝑦𝑒 𝑥 )} = { 𝑥 cos 𝑦 + 𝑦𝑒 𝑥 } = {cos 𝑦 𝑥 + 𝑦 𝑒 𝑥 }
𝜕𝑥 𝜕𝑥 𝜕𝑥 𝜕𝑥 𝜕𝑥 𝜕𝑥 𝜕𝑥 𝜕𝑥
𝜕 𝜕 𝜕
= {cos 𝑦 + 𝑦𝑒 𝑥 } = cos 𝑦 + 𝑦𝑒 𝑥 = 0 + 𝑦𝑒 𝑥 = 𝑦𝑒 𝑥
𝜕𝑥 𝜕𝑥 𝜕𝑥
𝜕 𝜕 𝜕 𝜕 𝜕 𝜕 𝜕 𝜕
𝑓𝑦𝑦 = { (𝑥 cos 𝑦 + 𝑦𝑒 𝑥 )} = { 𝑥 cos 𝑦 + 𝑦𝑒 𝑥 } = {𝑥 cos 𝑦 + 𝑒 𝑥 𝑦}
𝜕𝑦 𝜕𝑦 𝜕𝑦 𝜕𝑦 𝜕𝑦 𝜕𝑦 𝜕𝑦 𝜕𝑦
𝜕 𝜕 𝜕 𝑥 𝜕
= {−𝑥 sin 𝑦 + 𝑒 𝑥 } = (−𝑥 sin 𝑦) + 𝑒 = −𝑥 sin 𝑦 + 0 = −𝑥 cos 𝑦
𝜕𝑦 𝜕𝑦 𝜕𝑥 𝜕𝑦
𝜕 𝜕 𝜕 𝜕 𝜕
𝑓𝑦𝑥 = { (𝑥 cos 𝑦 + 𝑦𝑒 𝑥 )} = (cos 𝑦 + 𝑦𝑒 𝑥 ) = cos 𝑦 + 𝑦𝑒 𝑥 = − sin 𝑦 + 𝑒 𝑥
𝜕𝑦 𝜕𝑥 𝜕𝑦 𝜕𝑦 𝜕𝑦
𝜕 𝜕 𝜕 𝜕 𝜕 𝑥
𝑓𝑥𝑦 = { (𝑥 cos 𝑦 + 𝑦𝑒 𝑥 )} = (−𝑥 sin 𝑦 + 𝑒 𝑥 ) = (−𝑥 sin 𝑦) + 𝑒 = − sin 𝑦 + 𝑒 𝑥
𝜕𝑥 𝜕𝑦 𝜕𝑥 𝜕𝑥 𝜕𝑥
𝑒𝑦
Example 2.14: Find 𝑤𝑥𝑦 of 𝑤 = 𝑥𝑦 + 𝑦 2+1
Solution: 𝑤𝑥𝑦 states to differentiate first with respect to y and then with respect to x. since the
second term of w does not contain x, we can differentiate first with respect to x then with
respect to y:
7
Engineering Mathematics I Lecture 2: Partial Derivatives Prof. Dr. Emad Al-Hemiary
Second Year, First Semester 2021-2022
𝜕 𝜕 𝑒𝑦 𝜕 𝜕 𝜕 𝑒𝑦 𝜕
𝑤𝑥𝑦 = 𝑤𝑦𝑥 = { (𝑥𝑦 + 2 )} = { 𝑥𝑦 + 2
}= (𝑦 + 0) = 1
𝜕𝑦 𝜕𝑥 𝑦 +1 𝜕𝑦 𝜕𝑥 𝜕𝑥 𝑦 + 1 𝜕𝑦
Chain Rule
If 𝑤 = 𝑓(𝑥, 𝑦) has continuous partial derivatives 𝑓𝑥 and 𝑓𝑦 and if 𝑥 = 𝑥(𝑡), 𝑦 = 𝑦(𝑡) are
differentiable functions of 𝑡, then the composite 𝑤 = 𝑓(𝑥(𝑡), 𝑦(𝑡)) is a differentiable function
of 𝑡 and:
𝜕𝑤 𝜕𝑓 𝜕𝑥 𝜕𝑓 𝜕𝑦
= ∙ + ∙
𝜕𝑡 𝜕𝑥 𝜕𝑡 𝜕𝑦 𝜕𝑡
𝜕𝑤
Example 2.15: Evaluate for: 𝑤 = 𝑥 2 + 𝑦 2 , 𝑥(𝑡) = cos 𝑡 + sin 𝑡 , 𝑦(𝑡) = cos 𝑡 − sin 𝑡 using chain
𝜕𝑡
rule.
Solution: We apply chain rule:
𝜕𝑤 𝜕𝑓 𝜕𝑥 𝜕𝑓 𝜕𝑦
= ∙ + ∙
𝜕𝑡 𝜕𝑥 𝜕𝑡 𝜕𝑦 𝜕𝑡
𝜕𝑤 𝜕 2 𝜕 𝜕 2 𝜕
= (𝑥 + 𝑦 2 ) ∙ (cos 𝑡 + sin 𝑡) + (𝑥 + 𝑦 2 ) ∙ (cos 𝑡 − sin 𝑡)
𝜕𝑡 𝜕𝑥 𝜕𝑡 𝜕𝑦 𝜕𝑡
𝜕𝑤
= 2𝑥 ∙ (− sin 𝑡 + cos 𝑡) + 2𝑦 ∙ (− sin 𝑡 − cos 𝑡)
𝜕𝑡
= 2(cos 𝑡 + sin 𝑡) ∙ (− sin 𝑡 + cos 𝑡) + 2(cos 𝑡 − sin 𝑡) ∙ (− sin 𝑡 − cos 𝑡)
= 2(cos 𝑡 + sin 𝑡) ∙ (cos 𝑡 − sin 𝑡) − 2(cos 𝑡 − sin 𝑡) ∙ (cos 𝑡 + sin 𝑡) = 2{0} = 0
𝜕𝑤 𝑥 𝑦
Example 2.16: This is an example of three variables - Evaluate for: 𝑤 = 𝑧 + 𝑧 , 𝑥(𝑡) =
𝜕𝑡
1
cos 2 𝑡 , 𝑦(𝑡) = sin2 𝑡 , 𝑧 = 𝑡 using chain rule.